Activity of soil enzymes in rhizosphere of scots pine as a marker of the quality of wooded, formerly arable, soils = Aktywność enzymów glebowych w ryzosferze sosny zwyczajnej jako wskaźnik jakości zalesionych gleb porolnych - Bielińska, Elżbieta Jolanta; Węgorek, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this paper is the assessment of the influence of rhizosphere on the enzymatic activity of formerly arable soils afforested with Scots Pine (Pinus sylvestris L.). A comparison was made between the enzyme activity of formerly arable soils under 15-year-old and 51-year-old stands, and the enzyme activity of forest soils under 4-year-old cultivation and 104-year-old stands. It has been shown that the rhizosphere in formerly arable soils has considerable influence on the increase of enzyme activity cata-lysing the most important processes of organic substance change.
Keywords: zalesienia sosną zwyczajną; gleby porolne; enzymy glebowe; ryzosfera; afforestation; post-arable soils; enzymatic activity; rhizosphere